1995
DOI: 10.1083/jcb.130.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral expression and biological activities of GDNF, a new neurotrophic factor for avian and mammalian peripheral neurons.

Abstract: Abstract. Glial cell line-derived neurotrophic factor (GDNF) is a neurotrophic polypeptide, distantly related to transforming growth factor- , originally isolated by virtue of its ability to induce dopamine uptake and cell survival in cultures of embryonic ventral midbrain dopaminergic neurons, and more recently shown to be a potent neurotrophic factor for motorneurons. The biological activities and distribution of this molecule outside the central nervous system are presently unknown. We report here on the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
343
2
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(373 citation statements)
references
References 52 publications
22
343
2
6
Order By: Relevance
“…Our understanding of the mammalian spermatogonial stem cell niche has recently greatly progressed with the discovery that glial cell line-derived neurotrophic factor (Gdnf), a neurotropic factor secreted by glial cells in the brain, is also expressed in other organs during development, including ovary and testis Hellmich et al, 1996;Trupp et al, 1995;Golden et al, 1999). Gdnf, secreted by Sertoli cells after birth, is so far the only known paracrine factor in the testis specifically responsible for the maintenance and selfrenewal of SSCs in vivo and in vitro (Meng et al, 2000;Kubota et al, 2004b;Hofmann et al, 2005b).…”
Section: Spermatogenesis and The Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…Our understanding of the mammalian spermatogonial stem cell niche has recently greatly progressed with the discovery that glial cell line-derived neurotrophic factor (Gdnf), a neurotropic factor secreted by glial cells in the brain, is also expressed in other organs during development, including ovary and testis Hellmich et al, 1996;Trupp et al, 1995;Golden et al, 1999). Gdnf, secreted by Sertoli cells after birth, is so far the only known paracrine factor in the testis specifically responsible for the maintenance and selfrenewal of SSCs in vivo and in vitro (Meng et al, 2000;Kubota et al, 2004b;Hofmann et al, 2005b).…”
Section: Spermatogenesis and The Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor (GDNF), a member of the transforming growth factor-␤ superfamily, was initially isolated on the basis of its potent trophic effects on midbrain dopaminergic neurons in vitro (Lin et al, 1993, and subsequently was shown to be a potent trophic factor for a subset of sensory neurons as well as for sympathetic and parasympathetic neurons (Buj-Bello et al, 1995;Ebendal et al, 1995;Oppenheim et al, 1995;Trupp et al, 1995;Maxwell et al, 1996;Matheson et al, 1997;Molliver et al, 1997;Bennett et al, 1998). Early in development, all small dorsal root ganglion (DRG) neurons require nerve growth factor (NGF) for survival and express its receptors, trkA and p75.…”
Section: Introductionmentioning
confidence: 99%
“…GDNF mRNA is abundant in the epidermis (Trupp et al, 1995;Botchkareva et al, 2000), and a subset of epidermal nociceptive fibers is dependent on GDNF (Molliver et al, 1997). In peripheral nerves, Schwann cells express mRNA for GDNF and are also presumed to be a source of GDNF for peripheral neurons (Springer et al, 1994;Choi-Lundberg and Bohn, 1995;Ohi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, injured adult MNs responded to GDNF following axotomy in the facial nucleus of adult rats . In the PNS, GDNF promoted the survival and neurite outgrowth of sympathetic neurons, parasympathetic ciliary ganglion neurons, and sensory dorsal root ganglion neurons (Trupp et a!., 1995;Ebendal et a!., 1995).…”
mentioning
confidence: 97%